O processo de certificação integrada como agente alavancador de um desempenho superior de performance organizacional: o caso da unidade de negócio da Bacia de Campos (UN-BC) - Silva, Agostinho da Mota Robalinho da (2003)
This dissertation intends to present how lhe administration of SMS in the organizations developed along the years, composing a panorama of this evolution until the introduction of lhe current Management Systems that will have outstanding approach. lt trios to demonstrate lhat ts introduction facilitates lhe conquest of countless beneflts, presenting measurable results. contributing to increase lhe confidence that lhe adoption of Integrated Management Systems under eadership and sponsorship of lhe High Administration is a decision aligned with the managerial inlerests, and what today is a strategy wiIl be certainly IR the futuro an indispensable condition of the business. t also tries to demonstrate that lhe benefits dont delay to be seen, benefits that, in lhe study of case of Campos Basin were validated and attested by independent entities and according to approaches of international acceptance, through lhe most modern modeis of administration s evaluation lt presents a quahtative and quantitative analysis of results and the success of the strategy of the introduclion of Integrated Management System of Health, Safety and Environment certificate, to manage SMS subjects. This work ntends to offer lhe certainty that the Certified Management Systems, incorporated to the administration and with the exercise of its fundamental precepts, are unequivocal warranties of continuous improvements, and offerin9 growing benetits for the Soei ety and to insta)) a new organizationai culture that prepares companies to a socially attitude more appropriate.